Ebeveyn Matematik Kaygısı Ölçeği Geliştirme Çalışması - Mutlu, Yılmaz; Sarı, Mehmet Hayri; Çam, Zekeriya (Muş Alparslan Üniversitesi, 2018)
The aim of this study is to develop a math anxiety scale to determinethe math anxiety levels of parents whose children are in primary school. Thestudy was conducted by descriptive method. The data of the study gathered from408 people (276 mothers and 132 fathers). The three-dimensional structure obtained in the AFA analysis was alsoconfirmed by the DFA test.The fit index values obtained in this context werecalculated as ?2/df = 2.74, RMSEA = .104, NFI = .92, NNFI = .94, CFI= .95, IFI = .95, GFI = .82 and AGFI = .76 . When the obtained fit index valuesare examined, it can be said that Parental Math Anxiety Scale consisting of atotal of three dimensions and 16 items is a valid measurement tool. When allthe findings from the study are taken into account, it can be said that theParental Math Anxiety Scale is a valid and reliable measurement tool formeasuring the math anxiety levels of parents whose children are in primaryschool.

Bu çalışmada ilkokul düzeyinde öğrenim gören öğrencilerin ebeveynlerinin matematik kaygı düzeylerini belirlemeye yönelik ölçek geliştirmek hedeflenmiştir. Çalışma tarama yöntemi ile yürütülmüştür. Araştırmanın verileri çocuğu ilkokula devam eden 276 anne ve 132 baba olmak üzere toplam 408 kişiden toplanmıştır. AFA analizlerinde elde edilen üç boyutlu yapının DFA testi ile de doğrulandığı görülmüştür. Bu bağlamda elde edilen uyum indeksi değerleri ise ?2/Sd= 2.74, RMSEA= .104, NFI= .92, NNFI= .94, CFI= .95, IFI= .95, GFI= .82 ve AGFI= .76 olarak hesaplanmıştır. Elde edilen uyum indeksi değerleri incelendiğinde toplam üç boyut ve 16 maddeden oluşan Ebeveyn Matematik Kaygısı Ölçeği’nin (EMKÖ) çocukları ilkokula devam eden ailelerin matematik kaygısı düzeylerini ölçmede geçerli ve güvenilir bir ölçme aracı olduğu söylenebilir.
Development Study of Parental Math Anxiety Scale
anemon
Keywords: Math Anxiety; Parental Involvement; Parental Math Anxiety Scale; Scale Development; Matematik Kaygısı; Ebeveyn Katılımı; Ebeveyn Matematik Kaygısı Ölçeği; Ölçek Geliştirme